2009
DOI: 10.1515/znb-2009-0605
|View full text |Cite
|
Sign up to set email alerts
|

Skeleton Diversity by Cyclopropanation of Tricyclic Acylenamines

Abstract: Aiming at the structural diversification of phakellin-and isophakellin-type pyrrole-imidazole alkaloids on the skeleton level, the reaction of dipyrrolopyrazinones and pyrroloindolizines with dichlorocarbene was investigated. Conversions resulted in ring expansion affording novel chlorinated and brominated dipyrroloazepinones, pyridopyrroloazepinones, and dipyrrolopyrazinones. Structures of the tetracyclic products with hitherto unknown architectures have been secured by X-ray analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…To further clarify the role of the 4-amino-substituents in the autoxidation, the 4-unsubstituted tetrahydropyrrolo[2,3- f ]indolizin-9-one 29 was prepared by adopting Lindel’s approach to form the corresponding aldehyde 5d .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further clarify the role of the 4-amino-substituents in the autoxidation, the 4-unsubstituted tetrahydropyrrolo[2,3- f ]indolizin-9-one 29 was prepared by adopting Lindel’s approach to form the corresponding aldehyde 5d .…”
Section: Resultsmentioning
confidence: 99%
“…From a literature survey, Al-Mourabit and Lindel both demonstrated that the acid-promoted electrophilic aromatic substitution of N -[(pyrrol-2-yl)carbonyl]pyrrolidine-2-carbaldehydes effectively afforded the tricyclic pyrrolo[2,3- f ]indolizine skeleton (Scheme ). But their further elaboration at the C4- and C4a-positions of the pyrroloindolizine achieved only limited success.…”
Section: Introductionmentioning
confidence: 99%